2011
DOI: 10.1007/s12665-011-0953-8
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the sliding process of Donghekou landslide triggered by the Wenchuan earthquake using a distinct element method

Abstract: In the village of Donghekou (in Qingchuan County, Sichuan Province, China), a major landslide was triggered by the Wenchuan earthquake in 2008 with more than 10 9 10 6 m 3 of rock displaced. The kinematic behavior of this landslide is simulated using a 2D discrete element model. The numerical model used in this work is composed of discs bonded together. The initial boundary conditions are applied along the ball-wall contacts by using an initial velocity estimated from the strong motion data. The constraints ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Acknowledging the high mobility nature of Donghekou landslide, Li et al (2012) simulated its kinematic behavior, and concluded that a low friction coefficient (about 0.1) is required to justify its mobility. Zhou et al (2013) concluded that the maximum amplification coefficient of dynamic acceleration for the Donghekou landslide is approximately 3.909, and the sliding mass was triggered with a small initial velocity when it detached from the upper slope.…”
Section: Geotechnical Properties and Landslide Mobilitymentioning
confidence: 99%
“…Acknowledging the high mobility nature of Donghekou landslide, Li et al (2012) simulated its kinematic behavior, and concluded that a low friction coefficient (about 0.1) is required to justify its mobility. Zhou et al (2013) concluded that the maximum amplification coefficient of dynamic acceleration for the Donghekou landslide is approximately 3.909, and the sliding mass was triggered with a small initial velocity when it detached from the upper slope.…”
Section: Geotechnical Properties and Landslide Mobilitymentioning
confidence: 99%
“…Meanwhile, numerical simulations based on various investigations were also applied to analyze the movement processes (Li et al, 2012;Zhang et al, 2012). However, the kinematic processes controlling the moving mass and the mechanism for some special phenomena associated with this huge landslide are still poorly understood because of the complicated movement processes and unique type.…”
Section: Introductionmentioning
confidence: 99%
“…Several models have been developed and applied to practical work. They use the discontinuous deformation analysis (DDA) method 29–31 , the finite element method (FEM) 32,33 , the discrete element method (DEM) 34,35 , the smoothed particle hydrodynamics method (SPH) 7,9 , to analyse the stability and simulate the failure process of the landslide. Some other studies also incorporate hydraulically based models to simulate landslide behaviour, such as DDA-SPH coupled method 36 and shallow water assumption-based model 37 .…”
Section: Introductionmentioning
confidence: 99%